Apical size reduction by macropinocytosis alleviates tissue crowding - Enzo Bresteau; Eve E. Suva; Christopher Revell; Osama A. Hassan; Aline Grata; Jennifer Sheridan; Jennifer Mitchell; Constadina Arvanitis; Farida Korobova; Sarah Woolner; Oliver E. Jensen; Brian Mitchell (Nature Communications, 2025)
Abstract Tissue crowding represents a critical challenge to epithelial tissues, which often respond via the irreversible process of live cell extrusion. We report that apical size reduction via macropinocytosis serves as a malleable and less destructive form of tissue remodeling that can alleviate the need for cell loss. We find that macropinocytosis is triggered by tissue crowding via mechanosensory signaling, leading to substantial internalization of apical membrane. This drives a reduction in apical surface which alleviates crowding. We report that this mechanism regulates the long-term organization of the developing epithelium and controls the timing of proliferation-induced cell extrusion. Additionally, we observe a wave of macropinocytosis in response to acute external compression. In both scenarios, inhibiting macropinocytosis induces a dramatic increase in cell extrusion suggesting cooperation between cell extrusion and macropinocytosis in response to both developmental and external compression. Our findings implicate macropinocytosis as an important regulator of dynamic epithelial remodeling.